تأثير التدريس باسلوب التعلم التعاوني في خفض مستوى القلق في تعلم مهارة الارسال التنسي بالكرة الطائرة - مطرود، حازم أحمد; الياس، انتظار فاروق (جامعة الموصل - كلية التربية الرياضية, 2010)
يهدف البحث الكشف عن: \ -تأثير استخدام أسلوب التعلم التعاوني في خفض مستوى القلق لدى طالبات المرحلة الإعدادية بالكرة الطائرة. \ -فاعلية التدريس باستخدام أسلوب التعلم التعاوني في تعليم مهارة الإرسال التنسي، ووضع الباحثان الفروض الآتية: \ -توجد فروق ذات دلالـة معنوية بين مجمـوعتي البحث (التجريبيـة والضابطة) في خفـض مستوى القلق لـدى طالبات المرحلـة الإعدادية بالكرة الطائرة. \ -توجد فروق ذات دلالة معنوية بين مجموعتي البحث (التجريبية والضابطة) في تعلم مهارة الإرسال التنسي. \ استخدم الباحثان المنهج التجريبي لملاءمته طبيعـة البحـث، أمـا عينـة البحـث فقـد تكونـت مـن طالبـات شـعبتين تـم اختيـارهم عشوائيا من المرحلة الخامسة والبالغ عددهن ثلاث شعب وبواقع (١٦) طالبة لكل شعبة بعد أن استبعد الباحثان عدد من أفراد عينة البحـث وذلـك لعـدم تجانـسهم مـع أفـراد عينـة البحـث، وبهـذا شـكلت العينـة نـسبة مئويـة مقـدارها (٧٨.٣٦ %) مـن مجتمـع البحـث الأصـلي وهي نسبة مناسبة وتم التكـافؤ بين المجموعات في متغيرات (العمر، الطـول، الكتلة، وبعض عناصر اللياقة البدنية والحركية) المؤثرة في تعلم مهارة الإرسال المواجه من الأعلى "التنسي". واعتمد الباحثان التصميم التجريبي الذي يطلق عليه تصميم المجموعـات المتكافئـة العـشوائية الاختبـار ذات الملاحظـة القبليـة والبعديـة. اسـتغرق تنفيـذ المنهـاج التعليمـي وبعـد إجـراء التجربـة الاستطلاعية تم تنفيذ التجربة الرئيسية يوم السبت ٢٨/٣/٢٠٠٩ ولمدة (٤) أسابيع وبمعدل (٨) وحدات تعليمية للمجمـوعتين وزمـن كـل وحـدة تعليميـة (٤٥) دقيقـة. وبعـد جمـع البيانـات وتفريغهـا تمـت معالجتهـا إحـصائيا باسـتخدام (الوسـط الحـسابي، الانحـراف المعياري، النسبة المئوية، اختبار(ت) لعينتين متساويتين). \ واستنتج الباحثان ما يأتي: \ 1. إن أسلوب التعلم التعاوني هو أسلوب فعال في تعليم الطالبات فن الأداء لمهارة الإرسال التنسي. \ 2. تفوق أسلوب التعلم التعاوني على الأسلوب (التقليدي) في تعلم مهارة الإرسال التنسي. \ وأوصى الباحثان بما يأتي: \ 1. التأكيد على استخدام أسلوب التعلم التعاوني لتعلم مهارات الكرة الطائرة. \ 2. اجراء دراسات مماثلة على مهارات أخرى بالكرة الطائرة. Aims of this research: \ - Check up the influence of cooperative learning in reducing the anxiety level of high school female students, in volleyball. \ - Checkup the activity of using cooperative learning method in learning the tennis transmission skill. \ The researchers supposed the following: \ - There are many abstract content differences between the tow groups of research (experimental and control) about the activity of cooperative learning in reducing the anxiety level of high school female students. \ - There are many abstract content differences between the tow groups of research about the activity of teaching by use the cooperative method in learning tennis transmission skill. \ The researchers used the experimental method for its suitability to the research complexion, the specimen consisted of female students from tow groups of fifth class that had been choosen randomly from three groups (16 students from each groups), after elimination some of them because the were unlikeness with the others. \ This specimen formed a good rate of (% 36.78) per cent form the total basic research. The parity between the groups was made in variable of (ago, length, cluster, and some elements of physical fitness and motor skills) affecting in learning the tennis transmission skill that opposite the top. \ The researchers depended on the experimental design which called ((the design of randomly checkup equivalent groups that have following and anteriority notation)). \ This curriculum had been done in Saturday 28/march/ 2009 , in (4) weeks at the rate of (6) education units, (45) minute for each one after collection and evacuation, the data had been processed statically by using (arithmetic mean, standard deviation, percent, and (T) test for two equal specimens. \ Conclusion: \ The researcher's conctuded the following:- \ -The cooperative learning is an active method for teaching the female students the transmission skill technically. \ - The progress of the cooperative learning method on the classical one, in learning the tennis transmission skill. \ The researcher recommended the following: \ 1. Stress on using the cooperative learning method to learn skills of volleyball. \ 2. Making similar studies of other skills in volleyball.
Keywords: التعلم التعاوني -- القلق -- الكرة الطائرة -- طرق التدريس